A method for strengthening and toughening a wrought rare earth magnesium alloy
Patent Information
- Application Number
- CN202310137433.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-20
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2043-02-20
AI Technical Summary
[0005]在已公开的技术中,中国专利CN109594028A公开的“一种高性能变形稀土镁合金增韧的形变热处理方法”,其采用了一种预制热处理的手段来提升镁合金的塑性,即对镁合金进行了变形前的高温预退火处理,使其析出大量的粗大的Mg5RE相来促进变形过程中的动态再结晶行为,尽管改善了合金的延展性却降低了强度
[0037](1)更好地调节了坯料中第二相分布。本发明所述工艺与传统的变形前热处理工艺相比,增加了多级时效处理工艺,让稀土镁合金坯料分级析出LPSO相、γ’相和β’相,合理调控其含量和体积分数(层状LPSO相体积分数约为0-40vol%、针状γ’相体积分数约为5-30vol%、凸镜状β’相体积分数约为40-85vol%),最终使它们相互配合起到了改善镁合金成形性,调整变形组织和织构的效果。而传统的工艺只是在挤压变形前溶解共晶相和单一的析出LPSO相或β’相,难以有效调控其含量和比例,不能充分发挥各种第二相的优势,导致最终得到的变形组织和力学性能均不够理想。
Smart Images

Figure CN118516630B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of magnesium alloy technology, and specifically relates to a method for strengthening and toughening deformed rare earth magnesium alloys. Background Technology
[0002] Magnesium has a density only 1 / 4 that of steel and 2 / 3 that of aluminum. Its alloys have the characteristics of high specific strength, good damping and shock absorption performance, and excellent electromagnetic shielding. It is recognized internationally as one of the most promising lightweight materials. It plays a pivotal role in solving the lightweighting problem of key equipment and major projects in my country, and is of great significance in alleviating my country's increasingly severe environmental and energy crisis.
[0003] In recent years, magnesium alloys have been successfully used as a lightweight alternative to aluminum alloys in the rail transit field for non-critical components such as vehicle seats, brackets, trays, and housing shells. However, they still have disadvantages such as low absolute strength at room temperature and poor plasticity. In order to ensure their further promotion and application in key structural components, it is urgent to further develop magnesium alloy reinforcement and toughening technology, especially wrought rare earth magnesium alloy reinforcement and toughening technology.
[0004] Currently, there are two main methods for strengthening and toughening magnesium alloys: one is to adjust the microstructure and improve the micromorphology through plastic deformation; the other is to precipitate a second phase and pin dislocations to increase strength through heat treatment.
[0005] Among the publicly disclosed technologies, Chinese patent CN109594028A discloses "a deformation heat treatment method for toughening high-performance deformable rare earth magnesium alloys". It adopts a pre-heat treatment method to improve the plasticity of magnesium alloys, that is, the magnesium alloy is subjected to high-temperature pre-annealing treatment before deformation, which causes a large amount of coarse Mg5RE phase to precipitate to promote dynamic recrystallization behavior during deformation. Although it improves the ductility of the alloy, it reduces the strength.
[0006] Chinese patent CN113444946A discloses "A high-strength and tough rare-earth magnesium alloy and its processing method," which uses a post-deformation vibration aging heat treatment method to improve the strength and plasticity of magnesium alloys. Specifically, it involves performing an aging-annealing-secondary aging heat treatment on the deformed magnesium alloy to precipitate nano-LPSO phase and β' phase with a high number density to improve the mechanical properties of the alloy. However, the intermediate annealing process may cause grain growth and coarsening, destroying the deformed structure, and is not suitable as a strengthening and toughening method for magnesium alloys used in key components.
[0007] Therefore, based on the above research background and needs, how to obtain deformed rare earth magnesium alloys with excellent deformable microstructure and both strength and toughness through process control is the current research direction. Summary of the Invention
[0008] The purpose of this invention is to provide a method for strengthening and toughening wrought rare earth magnesium alloys. This method only requires controlling the heat treatment process before deformation and does not require changing the extrusion parameters to adjust the microstructure of the wrought rare earth magnesium alloy. This allows the wrought rare earth magnesium alloy to obtain various morphologies of deformed microstructures, achieving a significant simultaneous improvement in the strength and plasticity of the magnesium alloy. The obtained wrought rare earth magnesium alloy has an ultimate tensile strength ≥470MPa, a yield strength ≥370MPa, and an elongation ≥10%, meeting the service requirements of magnesium alloys for key structural components such as rail transit vehicle body support beams.
[0009] To achieve the above objectives, the technical solution of the present invention is as follows:
[0010] A method for strengthening and toughening wrought rare-earth magnesium alloys includes the following steps:
[0011] 1) Blank preparation
[0012] Obtain a blank suitable for the mold size from a rare earth magnesium alloy ingot;
[0013] 2) Supersaturated solution treatment
[0014] The billet is placed in a heat treatment furnace for solution treatment. After the solution treatment is completed, in order to prevent defects caused by a sudden drop in temperature, the billet is cooled to room temperature with water at a temperature ≥85℃. The solution treatment temperature is 480~530℃ and the solution treatment time is 12~24h.
[0015] 3) Timeliness processing
[0016] The supersaturated solid solution billet is placed in an aging furnace for multi-stage aging treatment, and then water-cooled to room temperature; the multi-stage aging treatment includes two stages, with the first stage aging temperature being 350-400℃ and the holding time being 0-20h, and the second stage aging temperature being 175-250℃ and the holding time being 50-150h.
[0017] 4) Extrusion deformation
[0018] The aged billet is preheated to the extrusion deformation temperature and held at that temperature. Then it is placed in a preheated and held extrusion die for extrusion deformation to obtain the extruded and deformed sample.
[0019] 5) Aging treatment after deformation
[0020] After extrusion deformation, the sample is placed in an aging furnace for heat treatment at a temperature of 180–225℃ for 40–150 hours. After treatment, it is cooled to room temperature with water.
[0021] Preferably, the rare earth magnesium alloy ingot is a Mg-Gd-Y-Zn-Mn alloy obtained by a semi-continuous casting process.
[0022] Preferably, the Mg-Gd-Y-Zn-Mn alloy has the following composition by mass percentage: Gd 8.0-10.0%, Y 4.0-5.0%, Zn 1.0-2.0%, Mn 0.4-1.0%, with the balance being Mg and other unavoidable impurities.
[0023] Furthermore, long-period phases and nano-second phases precipitate in the billet after the multi-stage aging treatment in step 3). The long-period phases include layered LPSO phases and needle-like γ' phases, and the nano-second phases are lenticular β' phases. The volume fraction of the layered LPSO phase is 0-40 vol%, the volume fraction of the needle-like γ' phase is 5-30 vol%, and the volume fraction of the lenticular β' phase is 40-85 vol%.
[0024] Furthermore, the microstructure of the deformed rare earth magnesium alloy is a fine equiaxed recrystallized microstructure with a volume percentage of ≥80 vol%, or a bimodal microstructure composed of fine equiaxed recrystallized grains and fine columnar deformed grains. The size of the recrystallized grains is ≤10 μm, preferably ≤5 μm; the size of the deformed grains is ≤25 μm, preferably ≤15 μm.
[0025] Furthermore, the microstructure of the deformed rare earth magnesium alloy is a fine equiaxed recrystallized structure with a volume percentage of ≥90 vol%, preferably 95-98 vol%.
[0026] Furthermore, when the deformed rare-earth magnesium alloy has a bimodal structure consisting of fine equiaxed recrystallized grains and fine columnar deformed grains, the volume percentage of the deformed grains is 40–75 vol%.
[0027] Furthermore, the deformed rare earth magnesium alloy has a yield strength ≥370MPa, an ultimate tensile strength ≥470MPa, and an elongation ≥10%.
[0028] In the strengthening and toughening treatment method for deformed rare earth magnesium alloys described in this invention:
[0029] Steps 1) through 3) are all blank processing steps before extrusion deformation.
[0030] Step 1) is to obtain a blank suitable for the size of the extrusion die.
[0031] Step 2): The billet undergoes solution heat treatment at a temperature controlled between 480 and 530°C for 12 to 24 hours, longer than conventional solution treatment. This process dissolves the eutectic phases that are detrimental to the formability and mechanical properties of the material, while maximizing the retention of dissolved elements within the billet. This results in a supersaturated magnesium matrix, facilitating the precipitation of the second phase during subsequent multi-stage aging processes. Water at ≥85°C is used to cool the billet to room temperature to prevent microcracks caused by excessively low cooling water temperature.
[0032] In step 3), a multi-stage aging treatment is employed. The first-stage aging temperature is controlled at 350–400℃, with a holding time of 0–20 h. The second-stage aging temperature is controlled at 175–250℃, with a holding time of 50–150 h. LPSO phase tends to precipitate in the high-temperature range (350–400℃), while γ' and β' phases tend to precipitate in the low-temperature range (175–250℃), thus allowing LPSO, γ', and β' phases to precipitate in a graded manner in the rare-earth magnesium alloy billet. By controlling the aging temperature and time, the content and volume fraction of each phase in the billet can be precisely controlled, resulting in the precipitation of a certain volume fraction of layered LPSO phase (0–40 vol%), needle-like γ' phase (5–30 vol%), and lenticular β' phase (40–85 vol%) in the magnesium matrix.
[0033] The LPSO phase can coordinate strain through a torsion mechanism, reduce stress concentration, and inhibit the initiation of microcracks during deformation, thereby improving the formability of the material and facilitating subsequent extrusion deformation. The γ' and β' phases can promote dynamic recrystallization through a particle-stimulated nucleation mechanism, and some of them undergo dynamic dissolution during deformation, attaching to the grain boundaries of dynamic recrystallization and generating solute resistance, thus inhibiting the growth of dynamically recrystallized grains. By utilizing the interaction of different second phases during extrusion to influence the dynamic recrystallization behavior of the magnesium matrix, the deformation microstructure and texture can be improved. Furthermore, the uniformly precipitated second phases before deformation cause dislocations to become orderly pinned and dynamically dissolve as strain increases, enhancing the aging precipitation effect after deformation and resulting in a synergistic improvement in the strength and plasticity of the magnesium alloy.
[0034] Step 4) Extrusion deformation can further reduce internal defects in the material, while improving the material properties through deformation strengthening effect. In addition, it can also dissolve some of the second phase into the matrix through the dynamic effect during the deformation process, thereby improving the precipitation effect after deformation and aging.
[0035] After being processed through a complete set of processes, rare earth magnesium alloys can achieve a good synergistic effect of heat treatment strengthening and deformation strengthening, thereby improving the strength and plasticity of deformed rare earth magnesium alloys in a coordinated manner.
[0036] Compared with the traditional homogenization-extrusion-aging strengthening process, the present invention has the following advantages:
[0037] (1) Better regulation of the distribution of the second phase in the billet. Compared with the traditional pre-deformation heat treatment process, the process described in this invention adds a multi-stage aging treatment process, which allows the rare earth magnesium alloy billet to precipitate LPSO phase, γ' phase and β' phase in stages, and reasonably controls their content and volume fraction (the volume fraction of layered LPSO phase is about 0-40 vol%, the volume fraction of needle-like γ' phase is about 5-30 vol%, and the volume fraction of lenticular β' phase is about 40-85 vol%). Ultimately, they work together to improve the formability of magnesium alloy and adjust the deformation structure and texture. In contrast, the traditional process only dissolves the eutectic phase and precipitates a single LPSO phase or β' phase before extrusion deformation, which makes it difficult to effectively control their content and proportion, and cannot give full play to the advantages of various second phases, resulting in less than ideal deformation structure and mechanical properties.
[0038] (2) It has a more significant age-strengthening effect. During extrusion, billets treated with traditional processes undergo dynamic precipitation, forming a large number of layered long-period phases and β phases, which reduces the elemental content in the matrix and is detrimental to the precipitation of nano-second phases during subsequent aging. The multi-stage aging process of this invention effectively regulates the second phase in the billet, inducing it to form a good deformable structure during extrusion. It also allows the second phase precipitated before deformation to dynamically dissolve during deformation, retaining more solute atoms in the matrix and enhancing the subsequent age-strengthening effect. Ultimately, this coordinates the pre-deformation heat treatment, plastic deformation, and post-deformation heat treatment, forming a complete strengthening and toughening process for deformed rare-earth magnesium alloys.
[0039] (3) It can prepare more diverse deformed microstructures. Traditional processes often produce bimodal microstructures composed of coarse deformed grains (grain size ≥ 30 μm) and recrystallized grains. This type of microstructure often exhibits a pronounced basal texture and is prone to instability and cracking during subsequent secondary processing. However, this invention only requires controlling the process parameters of the heat treatment before deformation, without changing the extrusion parameters, to adjust the microstructure. The resulting magnesium alloy microstructure is a fine equiaxed recrystallized microstructure or a bimodal microstructure composed of fine equiaxed recrystallized grains and fine columnar deformed grains, wherein the recrystallized grain size is ≤ 10 μm and the deformed grain size is ≤ 25 μm, such as... Figure 7-10 As shown in the figure. In these structures, the fine equiaxed recrystallized grains can not only exert a fine-grain strengthening effect, but also coordinate strain to promote the activation of the slip system; while the fine columnar deformed grains can act as short fiber reinforcement in the matrix, so that the material can basically maintain its original strength after dynamic recrystallization and softening.
[0040] (4) It has more balanced comprehensive mechanical properties. The rare earth magnesium alloy obtained by the present invention through solution heat treatment-multi-stage aging treatment-extrusion deformation-post-deformation aging treatment process has an ultimate tensile strength ≥470MPa, yield strength ≥370MPa, and elongation ≥10%. Compared with the rare earth magnesium alloy obtained by the traditional homogenization-extrusion-aging treatment process, the elongation is increased by 65% without reducing the strength. The obtained rare earth magnesium alloy has both high strength and high ductility, which meets the service requirements of magnesium alloy for key structural components such as rail transit vehicle body support beams. Attached Figure Description
[0041] Figure 1 This is a metallographic diagram of the supersaturated solid solution state of the rare earth magnesium alloy in Example 1 of the present invention.
[0042] Figure 2 This is a partially enlarged view of the metallographic structure of the rare earth magnesium alloy in supersaturated solid solution state in Example 1 of the present invention.
[0043] Figure 3-6 The images shown are transmission microstructures of rare earth magnesium alloys from Examples 1-4 of this invention after undergoing multi-stage aging treatment.
[0044] Figure 7-10 The images shown are metallographic diagrams of rare earth magnesium alloys obtained in Examples 1-4 of this invention.
[0045] Figure 11 The image shows the metallographic structure of the rare earth magnesium alloy in the extruded state, as shown in Comparative Example 1.
[0046] Figure 12 This is a comparison curve of the tensile mechanical properties of magnesium alloys obtained by the process described in this invention and magnesium alloys obtained by conventional processes. Detailed Implementation
[0047] The present invention will be further described below with reference to the embodiments and accompanying drawings, but the embodiments of the present invention are not limited thereto.
[0048] The magnesium alloy composition of the embodiments and comparative examples of the present invention is shown in Table 1, with the balance being Mg and unavoidable impurities; the specific process parameters of the embodiments of the present invention are shown in Table 2; the properties of the magnesium alloys obtained in the embodiments and comparative examples of the present invention are shown in Table 3.
[0049] Example 1
[0050] A method for strengthening and toughening wrought rare-earth magnesium alloys includes the following steps:
[0051] 1) Blank preparation
[0052] The required billet with a diameter of 87mm and a height of 40mm is obtained from rare earth magnesium alloy ingots by mechanical cutting.
[0053] 2) Supersaturated solution treatment
[0054] The billet is placed in a heat treatment furnace for solution treatment. After the solution treatment is completed, the billet is cooled to room temperature with water at a temperature ≥85℃. The solution treatment temperature is 530℃ and the solution treatment time is 16h.
[0055] 3) Multi-level timeliness processing
[0056] The supersaturated solid solution billet is placed in an aging furnace for multi-stage aging treatment, and then water-cooled to room temperature; the multi-stage aging treatment includes two stages, with the first stage aging temperature being 380℃ and the holding time being 15h, and the second stage aging temperature being 250℃ and the holding time being 96h.
[0057] 4) Extrusion deformation
[0058] The aged billet was preheated to the extrusion deformation temperature of 420℃ and held for 10 minutes. Then it was placed in an extrusion die that had been preheated to 430℃ and held for extrusion deformation. The extrusion ratio was 11:1 and the extrusion rate was 1 mm / s.
[0059] 5) Aging treatment after deformation
[0060] The extruded and deformed specimens were placed in an aging furnace for heat preservation and aging treatment. After the treatment, they were cooled to room temperature with water. The aging treatment temperature after deformation was 180℃ and the aging treatment time was 150h.
[0061] Comparative Example 1
[0062] The traditional homogenization-extrusion-aging strengthening process includes the following specific steps:
[0063] The billet prepared from the selected rare earth magnesium alloy has a diameter of 87 mm and a height of 40 mm.
[0064] 1) Homogenization treatment: The cast billet is homogenized in a constant temperature furnace at 520℃ for 24 hours, and then taken out and placed in hot water at ≥85℃ to cool.
[0065] 2) Extrusion deformation: After homogenization, the billet is preheated at 420℃ for 30 minutes and then placed into an extrusion die that has been preheated at 430℃ for 6 hours for extrusion deformation. The extrusion deformation temperature is 420℃, the extrusion ratio is 11:1, and the extrusion rate is 1mm / s.
[0066] 3) Aging treatment after deformation: The extruded billet is placed in a preheated aging furnace for aging treatment at 200℃. After 60 hours, it is taken out and cooled in water at 25℃.
[0067] Comparative Example 2
[0068] The steps are the same as those in Comparative Example 1, except that the homogenization time in step 1) is changed to 12 hours.
[0069] Comparative Example 3
[0070] The steps are the same as those in Comparative Example 1, except that the homogenization process in step 1) is changed to 500℃-8h+525℃-5h.
[0071] The obtained magnesium alloy samples were processed into tensile specimens for room temperature tensile testing. The specifications of the tensile specimens conformed to GB / T16865-2013, and the tensile testing method conformed to GB / T228.1-2010. The obtained mechanical properties are detailed in Table 2.
[0072] Figure 1 and Figure 2 The images show the metallographic structure of rare earth magnesium alloys in supersaturated solid solution state in Example 3 and Comparative Example 1 of this invention, respectively. It can be seen from the images that the eutectic phase in the billet is basically dissolved, with only a small amount of interdendritic LPSO phase precipitating from the grain boundaries. This indicates that the solid solution effect is good and the solute atoms in the matrix are basically saturated.
[0073] Figure 3-6 The images show transmission electron microstructures of rare earth magnesium alloys from Examples 1-4 of this invention after multi-stage aging treatment. As can be seen from the images, the second phase in the billet after multi-stage aging treatment mainly consists of layered LPSO phase with a 14H stacking structure, fine needle-like γ' phase, and lenticular β' phase. This invention successfully prepared a mixture containing stable LPSO, γ', and β' phases, and controlled their content and proportion (0-40 vol% volume fraction of layered LPSO phase, 5-30 vol% volume fraction of needle-like γ' phase, and 40-80 vol% volume fraction of lenticular β' phase) through solution heat treatment and multi-stage aging treatment processes. This fully utilizes the synergistic strengthening effect of each phase, while also considering the improvement in aging effect after deformation. This integrates pretreatment, plastic deformation, and post-treatment into a cohesive whole, solving the problem of achieving both strength and plasticity in magnesium alloys. Most other pre-deformation heat treatment processes only dissolve the eutectic phase and precipitate a single LPSO or β' phase, resulting in less than ideal microstructures and properties.
[0074] Figure 7-10 These are metallographic images of rare earth magnesium alloys obtained in Examples 1-4 of this invention, respectively. Figure 7 It can be seen that the microstructure of the magnesium alloy sample obtained in Example 1 of the present invention is mainly composed of fine recrystallized grains, with an average grain size of about 4.1 μm and a recrystallized grain volume fraction of about 95.7 vol%.
[0075] from Figure 8It can be seen that the microstructure of the magnesium alloy sample obtained in Example 2 of the present invention is mainly composed of fine recrystallized grains, while some large grains that have not fully recrystallized also exist. The average size of the recrystallized grains is about 6.5 μm, and the volume fraction of the recrystallized grains is about 82.3 vol%.
[0076] from Figure 9 It can be seen that the microstructure of the magnesium alloy sample obtained in Example 3 of the present invention consists of fine recrystallized grains (average size of 3.3 μm) and deformed grains (average size of 14.5 μm). The deformed grains are sufficiently refined and elongated into slender strips. The average grain size difference between the recrystallized grains and the deformed grains is about 11.2 μm, and the volume fraction of the recrystallized grains is about 40.3 vol%.
[0077] from Figure 10 It can be seen that the microstructure of the magnesium alloy sample obtained in Example 4 of the present invention consists of fine recrystallized grains and deformed grains.
[0078] Figure 11 The image shows the metallographic structure of the magnesium alloy sample obtained in Comparative Example 1. As can be seen from the image, the microstructure of the magnesium alloy sample obtained in Comparative Example 1 consists of recrystallized grains (average size 5 μm) and coarse deformed grains (average size 35.4 μm). The average grain size difference between the recrystallized grains and the deformed grains is approximately 30.4 μm, and the volume fraction of the recrystallized grains is 23.4 vol.
[0079] By comparing the metallographic structures of the embodiments of the present invention and the comparative examples, it can be found that the proportion of recrystallized grains in the magnesium alloy samples of the embodiments of the present invention is greater than that in the comparative examples, and the average grain size difference (the size difference between recrystallized grains and deformed grains) in the embodiments is smaller than that in the comparative examples. This indicates that the process used in the present invention can effectively refine the grains and improve the extrusion deformation structure, resulting in a finer and more uniform deformed rare earth magnesium alloy structure. The reason for this is that the LPSO phase, γ' phase, and β' phase in the billet of the embodiments of the present invention affect the microstructure evolution during the extrusion process, while the solution heat treatment and multi-stage aging treatment processes can more effectively control the content and proportion of these second phases, enabling them to better coordinate strain, influence dislocation movement and dynamic recrystallization behavior during deformation, and form a better extrusion structure.
[0080] Figure 12This is a comparison of the tensile mechanical properties of magnesium alloys obtained by the process described in this invention and those obtained by conventional processes. As can be seen from the figure, the magnesium alloy sample obtained by the conventional process has a yield strength of 384 MPa, an ultimate tensile strength of 519 MPa, and an elongation of 7.5%. Although this meets the strength requirements for rare-earth magnesium alloys used in rail transit, the elongation is significantly lower. In contrast, the magnesium alloy sample obtained by this invention has a yield strength of 387 MPa, an ultimate tensile strength of 521 MPa, and an elongation of 12.4%, representing an increase of approximately 65% in elongation compared to the conventional method. Therefore, the process described in this invention significantly increases the ductility of magnesium alloys without reducing strength, and even slightly improves it, resulting in a magnesium alloy material with both high strength and high ductility, meeting the performance requirements for rare-earth magnesium alloys used in rail transit.
[0081] In summary, this invention, without altering deformation parameters, successfully prepared a fully dynamically recrystallized microstructure and a bimodal microstructure containing deformed grains of different shapes and sizes by controlling the second phase in the billet through solution heat treatment and multi-stage aging treatment. This provides a new approach for microstructure control in deformed magnesium alloys. Furthermore, compared to traditional methods, the prepared magnesium alloy samples exhibit higher overall mechanical properties, more uniform and stable deformed microstructures, and better meet the requirements for magnesium alloys used in critical components.
[0082] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit the technical solutions. Those skilled in the art should understand that any modifications or equivalent substitutions to the technical solutions of the present invention without departing from the spirit and scope of the present invention should be covered within the scope of the claims of the present invention.
[0083]
[0084]
[0085]
Claims
1. A method for strengthening and toughening wrought rare earth magnesium alloys, comprising the following steps: 1) Blank preparation Obtain a blank suitable for the mold size from a rare earth magnesium alloy ingot; 2) Supersaturated solution treatment The billet is placed in a heat treatment furnace for solution treatment. After the solution treatment is completed, the billet is cooled to room temperature with water at a temperature ≥85℃. The solution treatment temperature is 480~530℃ and the solution treatment time is 12~24h. 3) Timeliness processing The supersaturated solid solution billet is placed in an aging furnace for multi-stage aging treatment, and then water-cooled to room temperature; the multi-stage aging treatment includes two stages, with the first stage aging holding temperature at 350~400℃ and the holding time at 0~20h, and the second stage aging holding temperature at 175~250℃ and the holding time at 50~150h. 4) Extrusion deformation The aged billet is preheated to the extrusion deformation temperature and held at that temperature. Then it is placed in a preheated and held extrusion die for extrusion deformation to obtain the extruded and deformed sample. 5) Aging treatment after deformation The extruded and deformed specimens were placed in an aging furnace and kept at a constant temperature for aging treatment. The aging treatment temperature was 180~225℃ and the aging treatment time was 40~150h. After the treatment, the specimens were cooled to room temperature with water. The rare earth magnesium alloy ingot is a Mg-Gd-Y-Zn-Mn alloy obtained by a semi-continuous casting process.
2. The method for strengthening and toughening deformed rare earth magnesium alloys as described in claim 1, characterized in that, The Mg-Gd-Y-Zn-Mn alloy has the following composition by mass percentage: Gd 8.0~10.0%, Y 4.0~5.0%, Zn 1.0~2.0%, Mn 0.4~1.0%, with the balance being Mg and other unavoidable impurities.
3. The method for strengthening and toughening deformed rare earth magnesium alloys as described in claim 1 or 2, characterized in that, After the aging treatment in step 3), long-period phases and nano-second phases precipitate in the billet. The long-period phases include layered LPSO phases and needle-like γ' phases, and the nano-second phases are lenticular β' phases. The volume fraction of the layered LPSO phase is 0-40 vol%, the volume fraction of the needle-like γ' phase is 5-30 vol%, and the volume fraction of the lenticular β' phase is 40-85 vol%.
4. The method for strengthening and toughening deformed rare earth magnesium alloys as described in claim 1, characterized in that, In step 4), the extrusion deformation temperature is 380~450℃, the extrusion ratio is 6~20∶1, and the extrusion rate is 0.1~1mm / s.
5. The method for strengthening and toughening deformed rare earth magnesium alloys as described in claim 1 or 4, characterized in that, In step 4), the billet is preheated to the extrusion deformation temperature and then held at that temperature for 10-20 minutes.
6. The method for strengthening and toughening deformed rare earth magnesium alloys as described in claim 1 or 4, characterized in that, In step 4), the mold insulation temperature is 10~20℃ higher than the extrusion deformation temperature.
7. A deformed rare-earth magnesium alloy obtained by the strengthening and toughening treatment method according to any one of claims 1 to 6, characterized in that, The microstructure of the deformed rare earth magnesium alloy is a fine equiaxed recrystallized structure with a volume percentage of ≥80 vol%.
8. The wrought rare earth magnesium alloy as described in claim 7, characterized in that, The microstructure of the deformed rare earth magnesium alloy is a fine equiaxed recrystallized structure with a volume percentage of ≥90 vol%.
9. The wrought rare earth magnesium alloy as described in claim 8, characterized in that, The recrystallized structure with fine equiaxed grains accounts for 95-98% of the volume percentage.
10. A deformed rare-earth magnesium alloy obtained by the strengthening and toughening treatment method according to any one of claims 1 to 6, characterized in that, The microstructure of the deformed rare-earth magnesium alloy is a bimodal structure composed of fine equiaxed recrystallized grains and fine columnar deformed grains. The size of the recrystallized grains is ≤10μm, and the size of the deformed grains is ≤25μm, wherein the volume percentage of the deformed grains is 40~75 vol%.
11. The wrought rare earth magnesium alloy as described in claim 10, characterized in that, The recrystallized grain size is ≤5μm.
12. The wrought rare-earth magnesium alloy as described in claim 10, characterized in that, The deformed grain size is ≤15μm.
13. The wrought rare-earth magnesium alloy according to any one of claims 7 to 12, characterized in that, The deformed rare earth magnesium alloy has a yield strength ≥370MPa, an ultimate tensile strength ≥470MPa, and an elongation ≥10%.
Citation Information
Patent Citations
Deformation heat treatment method for toughening high-performance deformation rare-earth magnesium alloy
CN109594028A
Rare earth magnesium alloy with high strength and toughness and treatment method thereof
CN113444946A